Implementing a Next Generation Library System - Green, Peter (35th Annual IATUL Conference, 2014)
Only a few years ago most library management systems were considered stable and mature and the focus of effort by library vendors and academic libraries was on developing and implementing client facing, web scale, discovery layers. These are now ubiquitous. However the rise and rise of electronic content and the growing complexity of managing that electronic content with systems developed last century has led to the current focus on developing and implementing next generation library management systems. These new library systems are being built from the ground up, encompassing all forms of content and subsuming more recently developed products, such as link resolvers. Implementing a new library management system is a major undertaking and not taken lightly. Curtin University Library made the decision in 2012 to implement a next generation library system - Alma from Ex Libris – and went live in February 2014. In this paper the author reflects on the strategic thinking that informed this decision and explores why vendors have invested so much in the development of new systems and why libraries are taking them up, teases out the benefits and risks of moving to a cloud based, multi-tenanted, software as a service product that has traditionally been hosted locally, weighs up the advantages and disadvantages of being early or late to the game, considers the impact of a rapid development methodology, and finally reflects on the expected gain after the pain.